Effect of Fish Oil Supplementation and Aspirin Use on Arteriovenous Fistula Failure in Patients Requiring Hemodialysis - Ashley Irish; Andrea K. Viecelli; Carmel M. Hawley; Lai Seong Hooi; Elaine M. Pascoe; Peta‐Anne Paul‐Brent; Sunil V. Badve; Trevor A. Mori; Alan Cass; Peter G. Kerr; David Voss; Loke‐Meng Ong; et al. (2017)
Vascular access dysfunction is a leading cause of morbidity and mortality in patients requiring hemodialysis. Arteriovenous fistulae are preferred over synthetic grafts and central venous catheters due to superior long-term outcomes and lower health care costs, but increasing their use is limited by early thrombosis and maturation failure. ω-3 Polyunsaturated fatty acids (fish oils) have pleiotropic effects on vascular biology and inflammation and aspirin impairs platelet aggregation, which may reduce access failure.To determine whether fish oil supplementation (primary objective) or aspirin use (secondary objective) is effective in reducing arteriovenous fistula failure.The Omega-3 Fatty Acids (Fish Oils) and Aspirin in Vascular Access Outcomes in Renal Disease (FAVOURED) study was a randomized, double-blind, controlled clinical trial that recruited participants with stage 4 or 5 chronic kidney disease from 2008 to 2014 at 35 dialysis centers in Australia, Malaysia, New Zealand, and the United Kingdom. Participants were observed for 12 months after arteriovenous fistula creation.Participants were randomly allocated to receive fish oil (4 g/d) or matching placebo. A subset (n = 406) was also randomized to receive aspirin (100 mg/d) or matching placebo. Treatment started 1 day prior to surgery and continued for 12 weeks.The primary outcome was fistula failure, a composite of fistula thrombosis and/or abandonment and/or cannulation failure, at 12 months. Secondary outcomes included the individual components of the primary outcome.Of 1415 eligible participants, 567 were randomized (359 [63%] male, 298 [53%] white, 264 [47%] with diabetes; mean [SD] age, 54.8 [14.3] y). The same proportion of fistula failures occurred in the fish oil and placebo arms (128 of 270 [47%] vs 125 of 266 [47%]; relative risk [RR] adjusted for aspirin use, 1.03; 95% CI, 0.86-1.23; P = .78). Fish oil did not reduce fistula thrombosis (60 [22%] vs 61 [23%]; RR, 0.98; 95% CI, 0.72-1.34; P = .90), abandonment (51 [19%] vs 58 [22%]; RR, 0.87; 95% CI, 0.62-1.22; P = .43), or cannulation failure (108 [40%] vs 104 [39%]; RR, 1.03; 95% CI, 0.83-1.26; P = .81). The risk of fistula failure was similar between the aspirin and placebo arms (87 of 194 [45%] vs 83 of 194 [43%]; RR, 1.05; 95% CI, 0.84-1.31; P = .68).Neither fish oil supplementation nor aspirin use reduced failure of new arteriovenous fistulae within 12 months of surgery.anzctr.org.au Identifier: CTRN12607000569404.